Fading connections: A phenomenological study of oncology nurses’ experiences of Missed Nursing Care during an infectious disease outbreak - Mahsa Pourshaban; Atefeh Allahbakhshian; Hadi Hasankhani (PLoS ONE, 2025)
Purpose Providing holistic and high-quality nursing care to oncology patients necessitates integrating care across physical, psychological, spiritual, and emotional domains. This study explored the meaning of oncology nurses’ experiences of missed nursing care during the COVID-19 pandemic. Methods This study employed a qualitative design based on Heidegger’s hermeneutic phenomenological approach as the foundational philosophical approach because of its focus on real-life experiences. The sample comprised fourteen nurses employed at various oncology departments in Iran. Data was collected from February 2023 to March 2025 with institutional permission and ethics committee approval (IR.TBZMED.REC.1401.1032). Data were collected through in-depth, semi-structured interviews. Data analysis was conducted concurrently with data collection following the approach outlined by Diekelmann et al. (1989). Standards for Reporting Qualitative Research (SRQR) were used. Results Fading connections between oncology nurses and patients, nursing managers, physicians, and the care environment have affected the quality of care and communication during the pandemic. Three subthemes include (1) care behaviors, (2) isolation in duty, and (3) disruption of care canvas and twelve meaning units were obtained. The most care deficits were primarily related to emotional and psychological support. Conclusion When human and professional relationships are compromised, the essence of nursing care is lost, and it risks being reduced to a mechanical, task-focused practice. The experiences of oncology nurses during the COVID-19 pandemic reveal significant gaps in nursing care that stem from professional, relational, and systemic challenges. Addressing these issues is crucial for improving nurse well-being and patient outcomes in future healthcare crises.